Computer‐controlled stimulation for functional magnetic resonance imaging studies of the neonatal olfactory system. (2nd August 2013) - Arichi, T; Gordon‐Williams, R; Allievi, A; Groves, AM; Burdet, E; Edwards, AD
Abstract: Aim: Olfactory sensation is highly functional early in human neonatal life, with studies suggesting that odours can influence behaviour and infant–mother bonding. Due to its good spatial properties, blood oxygen level–dependent (BOLD) contrast functional magnetic resonance imaging (fMRI) has the potential to rapidly advance our understanding of the neural activity which underlies the development of olfactory perception in this key period. We aimed to design an 'olfactometer' specifically for use with neonatal subjects for fMRI studies of odour perception. Methods: We describe a fully automated and programmable, fMRI compatible system capable of presenting odorant liquids. To prevent contamination of the system and minimize between‐subject infective risk, the majority of the olfactometer is constructed from single‐use, readily available clinical equipment. The system was used to present the odour of infant formula milk in a validation group of seven neonatal subjects at term equivalent postmenstrual age (median age 40 weeks). Results: A safe, reliable and reproducible pattern of stimulation was delivered leading to well‐localized positive BOLD functional responses in the piriform cortex, amygdala, thalamus, insular cortex and cerebellum. Conclusions: The described system is therefore suitable for detailed studies of the ontology of olfactory sensation and perception during early human brain development.